New chronology of the best developed loess/paleosol sequence of Hungary capturing the past 1.1 ma: Implications for correlation and proposed pan-Eurasian stratigraphic schemes. (1st July 2018) - Sümegi, P.; Gulyás, S.; Molnár, D.; Sümegi, B.P.; Almond, P.C.; Vandenberghe, J.; Zhou, L.; Pál-Molnár, E.; Törőcsik, T.; Hao, Q.; Smalley, I.; Molnár, M.; et al.
Abstract: In this paper, we are presenting a revised chronology of the best developed, longest (100 m) LPS in Hungary dating back 1.1 Ma: borehole Udvari-2A. It is based on a non-tuned age-depth model, built on the position of the Matuyama-Brunhes Boundary, Jaramillo and Olduvai Subchrons. Furthermore, on the assignment of formerly recorded uninterpreted geomagnetic reversals in both chrons. Other chronometric tools (AMS 14 C dating, biostratigraphy, tephrostratigraphy) yielding absolute ages and/or ensuring validation of these were also used. Records of a Middle Pleistocene gastropod index fossil Neostyriaca corynodes (400 -140 ka) facilitated verification of ages between MIS 10 and MIS 6. Multiple age control points at 15, 25, 27, 45, 120, 191, 362, 430, 670, 780, 900, 990, 1070 ka were established for the last ca. 1.1 Ma. The resulting chronology is the best resolved independent one so far among Danubian Basin LPSs. In light of our data, the S3-S4 units were fused as S3 in all Serbian, and some Romanian sites and re-correlated with MIS 9. The results also point to a misassignment of the S5 units at these sites to MIS 13–15 leading to erroneous conclusions regarding paleoclimatic conditions and cyclicity. In our new stratigraphic scheme, these S5 paleosols were taken to represent the S4 paleosol and recorrelated with MIS 11. Finally, an ideal stratigraphic column dating back 1.1 Ma for SW Hungary was constructed and correlated with the Chinese loess/paleosol sequence of Xifeng and the benthic oxygen isotope record down to MIS 31. Highlights: A new independent chronology for the past ca. 1 Ma of the best developed loess/paleosol sequence in Hungary is presented. Age-depth model based on multiple magneto-, bio-, tephrostratigraphical and 14 C data with high fidelity is built. Former pan-Eurasian stratigraphic marker horizon of MIS 13-15 is refuted. Some stratigraphic units assigned to MIS 11, 13-15 in this scheme are reassigned to MIS 9, MIS 11 in regional correlation. A new ideal stratigraphic column for SW Hungary is constructed reaching down to MIS 31.